2020
DOI: 10.3390/ijerph17155272
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Learner Motivation and Classroom Social Climate: A Mixed Methods Approach

Abstract: The aim of this study was to analyze how motivation and classroom social climate was enhanced in the teaching–learning context throughout a Pedagogical Model of Personal and Social Responsibility (TPSR) implementation using a mixed method approach. An educational program was applied during an academic year in a student sample of primary and secondary school. A total of 44 sessions with 54 participants, between 11 and 16 years old (M = 13.41 years, SD = 1.73) were video-recorded. A multilevel triangulation desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 46 publications
2
23
1
1
Order By: Relevance
“…From a practical and pedagogical point of view, Menéndez and Fernández-Río [ 32 ] suggest the importance of teachers applying methodologies in the educational context aimed at fostering the development of these variables through the use of pedagogical models such as cooperative learning [ 64 ], sports education [ 65 ], or teaching personal and social responsibility (TPSR) [ 66 ]. The latter has been applied in different educational contexts, such as in extracurricular activities [ 67 ], in the school environment in the area of physical education [ 68 ], and in the rest of the curricular subjects [ 7 ], demonstrating the effectiveness of its implementation to improve responsibility, autonomy, motivation, and school social climate [ 6 , 69 ]. In this way, the use of pedagogical approaches in the educational context can allow the necessary conditions to be reached to promote responsibility, BPN, and self-determined motivation of students in the classroom [ 32 ], creating a school social climate that favors the development of prosocial behavior among students, while decreasing antisocial and violent behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a practical and pedagogical point of view, Menéndez and Fernández-Río [ 32 ] suggest the importance of teachers applying methodologies in the educational context aimed at fostering the development of these variables through the use of pedagogical models such as cooperative learning [ 64 ], sports education [ 65 ], or teaching personal and social responsibility (TPSR) [ 66 ]. The latter has been applied in different educational contexts, such as in extracurricular activities [ 67 ], in the school environment in the area of physical education [ 68 ], and in the rest of the curricular subjects [ 7 ], demonstrating the effectiveness of its implementation to improve responsibility, autonomy, motivation, and school social climate [ 6 , 69 ]. In this way, the use of pedagogical approaches in the educational context can allow the necessary conditions to be reached to promote responsibility, BPN, and self-determined motivation of students in the classroom [ 32 ], creating a school social climate that favors the development of prosocial behavior among students, while decreasing antisocial and violent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, school social climate is understood as the perception of students and teachers regarding the quality of their classroom experiences [ 6 ], normally characterized by the establishment of satisfactory socio-affective interactions between them. This variable contributes to the formation of an adequate classroom environment within the teaching–learning process [ 7 ], with the intention of achieving greater social and academic performance [ 8 ], as well as reducing bullying and violence in schools [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of SDT, Vallerand's [19] hierarchical model indicates that the impact of social factors (e.g., responsibility or school social climate) is mediated by basic psychological needs (autonomy, competence, and relatedness) that are essential and inherent to each person [20], whose satisfaction or frustration of these needs can lead to a more or less self-determined motivation and generate different cognitive, behavioral, and affective consequences in people's lives [18]. In this line, research related to the assignment of autonomy and responsibility to students [21], found a key factor that can satisfy basic psychological needs [22], the school social climate [23], and experience of fun in class [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Manzano-Sánchez and Valero-Valenzuela [ 2 ] suggest the need to establish a direct relationship between responsibility and the school social climate. In recent years, the number of studies that analyzed this variable increased [ 23 , 29 ], finding a direct relationship with academic performance, intrinsic motivation, and basic psychological needs. Various research studies [ 11 , 30 ] indicate the importance of effective classroom management by teachers in creating a good learning climate and reducing both drop-out and failure.…”
Section: Introductionmentioning
confidence: 99%
“…Por el contrario, climas controladores tienden a frustrar las NPBs y provocar menor disfrute, mayores problemas de comportamiento o aprendizajes menos significativos (Franco & Coterón, 2017;Pérez-González et al, 2019;Reeve & Cheon, 2014;Taylor et al, 2010;Tsai et al, 2008). La mayoría de los estudios basados en la SDT en EF en los que se han evaluado los climas interpersonales se han centrado en autoinformes del profesorado o en la percepción del alumnado, siendo bastante menor el número de investigaciones que evalúan de forma observacional estos climas interpersonales (Smith et al, 2016) a pesar de la eficacia de los enfoques mixtos para ver cambios a lo largo del tiempo (Valero-Valenzuela et al, 2020). La observación sistemática ha sido definida como un método de cuantificación de variables en el que se establece un manual de codificación, un contexto de medición, unos métodos de muestreo y métricas antes de recopilar los datos (Yoder et al, 2018).…”
Section: Introductionunclassified